2000
DOI: 10.1212/wnl.55.9.1256
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal motor neuropathy improved by IVIg

Abstract: IVIg improved conduction block as well as subjective and objective clinical measures of function in patients with MMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
143
0
16

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(162 citation statements)
references
References 28 publications
3
143
0
16
Order By: Relevance
“…IVIG remains the treatment of choice for patients with MMN [5,[71][72][73][74][75][76]. IVIG is recommended as a first-line therapy, based on a meta-analysis of 4 randomized, double-blind, placebocontrolled, trials [73][74][75][76], involving a total of 34 patients: 78 % of study participants had a significant short-term improvement in strength, selected as primary outcome measure, following IVIG treatment compared with 4 % following placebo [77].…”
Section: Ivigmentioning
confidence: 99%
See 1 more Smart Citation
“…IVIG remains the treatment of choice for patients with MMN [5,[71][72][73][74][75][76]. IVIG is recommended as a first-line therapy, based on a meta-analysis of 4 randomized, double-blind, placebocontrolled, trials [73][74][75][76], involving a total of 34 patients: 78 % of study participants had a significant short-term improvement in strength, selected as primary outcome measure, following IVIG treatment compared with 4 % following placebo [77].…”
Section: Ivigmentioning
confidence: 99%
“…IVIG is recommended as a first-line therapy, based on a meta-analysis of 4 randomized, double-blind, placebocontrolled, trials [73][74][75][76], involving a total of 34 patients: 78 % of study participants had a significant short-term improvement in strength, selected as primary outcome measure, following IVIG treatment compared with 4 % following placebo [77]. Another RCT was conducted in the USA and Canada to assess the efficacy, safety, and tolerability of 10 % liquid IVIG in 44 patients with MMN [78].…”
Section: Ivigmentioning
confidence: 99%
“…Yet, this is clearly different in MMN, where PE and even more GS might worsen the course of the disease. [56][57][58][59] Paraproteinemic neuropathy is another rare subtype of inflammatory neuropathy. Here, demyelination is often associated with the presence of clonally restricted IgM antibodies directed against myelin.…”
Section: Plasma Exchange In Multiple Sclerosis Relapsesmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of IVIg in MMN, including a few placebocontrolled, double-blind trials. 36,37 Lack of improvement after one, or at most two treatments should be considered as a treatment failure. However, even with intensive IVIg therapy some patients had progression of neurologic deficits.…”
Section: Multifocal Motor Neuropathymentioning
confidence: 99%